What impact has the introduction of the ongoing achievement record and sign off mentor had on the robustness of mentors’ assessment practices? - Royal, Jan (2017)
This study investigated the impact of two changes on the assessment of student nurses in practice in one University in England; the introduction of the ongoing achievement record and the development of the sign off mentor role (NMC, 2008). As contemporary literature showed nurse mentors were failing to fail student nurses, these changes to assessment in nursing practice were introduced (Duffy, 2003; Gainsbury, 2010). A literature review was conducted to identify key themes in the nurse mentoring literature and led to the research question for the study;